Minerals provide divergent protection to carbon- and nitrogen-rich organic matter in fluvial sediments - Naiyu Zhang; Zhifei Liu; Baozhi Lin; Jiawang Wu; Guanghui Yu; Bohao Yin; Chen-Feng You; Fernando P. Siringan; Charlotte E. L. Thompson; Carsten W. Müller (Communications Earth & Environment)
Abstract Sorption to mineral surfaces is widely regarded as the dominant mechanism of organic matter (OM) preservation, yet it cannot fully explain the varying fates of terrestrially-derived OM during its transport from land to ocean. To investigate this question, here we performed microscale analyses of OM-mineral associations in the clay-sized fraction, a critical carrier for long-term carbon burial and terrestrial OM transport. Across diverse OM sources and mineral compositions, we identify a consistent chemical–spatial coupling: nitrogen-rich OM is closely associated with iron-rich mineral surfaces, while carbon-rich OM is primarily protected within aggregate pores. This coupling suggests that minerals stabilise different OM types through distinct mechanisms, potentially explaining their contrasting responses to environmental changes during transport from land to ocean. Our results challenge the prevailing focus on surface sorption alone and underscore the importance of microscale OM–mineral organisation in controlling the fates of terrestrial OM across Earth’s land–ocean interface.